Language Learner Language A Case of Seventh Semester Students of the English Department, Faculty of Education, Atma Jaya Catholic University Jakarta - Harsono, Y. M. (TEFLIN Journal, 2003)
This paper describes the language of the language learners-language learner language - especially the pronunciation of the seventh semester students of the English department, Faculty of Education, Atma Jaya Catholic University Jakarta. Four major sub-topics are discussed in this paper which include the definition of interlanguage, the factors affecting interlanguage, some research findings on inter-language, the result of observation, and the conclusion and suggestion. On the basis of the theoretical background and the result of the observation, it is concluded that: (I) the inaccurate pronunciation of the English of the learners is a natural one from the point of view of SLA, (2) L2 learning differs from first language acquisition in that it is seldom successful, (3) the incorrect pronunciation of the learners should not be considered as something that is not allowed to occur but should be realized as something natural, and (4) the pronunciation specific of the learners is mostly as a result of overgeneralization of the kind of rules of pronouncing the words.